Impact of hot environment on colostrum and milk composition - Bernabucci, U.; Basiricò, L.; Morera, P. (Cellular and Molecular Biology, 2013)
Under hot and warm environments productivity and reproduction efficiency of farm and wild animals are negatively affected. The negative effects of hot environments on animal health are responsible for the alteration of colostrum and milk production in term of quantity and quality. Colostrum and milk are nutrient-rich fluids secreted by the mammary gland of female mammals after giving birth and during growth and development of the young. Multiple factors influence the production and the composition of colostrum and milk, including species, breed, health status, feeding practices and environmental conditions. Colostrum and milk are not only a good source of macronutrients and micronutrients, but contains many biologically-active constituents. Colostrum and milk of various species differ widely in amounts and proportions of their principal constituents, especially comparing monogastric with ruminant animals because of the difference between their physiology and digestion. The interspecies variations in part reflect different adaptive strategies to environmental conditions and selective pressures of various species during the evolution. A limited number of studies documented the effects of hot condition on modification of colostrum and milk quality, in particular referred to nutrients and immunoglobulin composition, but no information are available on the effects of hot environment on nutraceutical properties and bioactive molecules content of colostrum and milk.